Diminazen Aceturate Protects Pulmonary Ischemia-Reperfusion Injury via Inhibition of ADAM17-Mediated Angiotensin-Converting Enzyme 2 Shedding - Wang, Li-Fang; Sun, Yang-Yang; Pan, Qian; Yin, Yi-Qing; Tian, Xiao-Ming; Liu, Yue; Bu, Tegeleqi; Zhang, Qingy; Wang, Yong-An; Zhao, Jing; Luo, Yuan (Frontiers in Pharmacology, 2021)
Lung ischemia-reperfusion (IR) injury is induced by pulmonary artery occlusion and reperfusion. Lung IR injury commonly happens after weaning from extracorporeal circulation, lung transplantation, and pulmonary thromboendarterectomy; it is a lethal perioperative complication. A definite therapeutic intervention remains to be determined. It is known that the enzyme activity of angiotensin-converting enzyme 2 (ACE2) is critical in maintaining pulmonary vascular tone and epithelial integrity. In a noxious environment to the lungs, inactivation of ACE2 is mainly due to a disintegrin and metalloprotease 17 (ADAM17) protein-mediated ACE2 shedding. Thus, we assumed that protection of local ACE2 in the lung against ADAM17-mediated shedding would be a therapeutic target for lung IR injury. In this study, we established both in vivo and in vitro models to demonstrate that the damage degree of lung IR injury depends on the loss of ACE2 and ACE2 enzyme dysfunction in lung tissue. Treatment with ACE2 protectant diminazen aceturate (DIZE) maintained higher ACE2 enzyme activity and reduced angiotensin II, angiotensin type 1 receptor, and ADAM17 levels in the lung tissue. Concurrently, DIZE-inhibited oxidative stress and nitrosative stress via p38MAPK and NF-κB pathways consequently reduced release of pro-inflammatory cytokines such as TNF-α, IL-6, and IL-1β. The underlying molecular mechanism of DIZE contributed to its protective effect against lung IR injury and resulted in the improvement of oxygenation index and ameliorating pulmonary pathological damage. We concluded that DIZE protects the lungs from IR injury via inhibition of ADAM17-mediated ACE2 shedding.